2023
DOI: 10.1039/d3ob00799e
|View full text |Cite
|
Sign up to set email alerts
|

C–H functionalization of pyridines

Abstract: Pyridine and its reduced form (piperidines) are the most common nitrogen heterocycles in FDA-approved drugs. Additionally, alkaloids, ligands for transition metals, catalysts, and organic materials with various properties make them...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…Notwithstanding the diverse range of alternatives offered by CÀ H bond functionalization, coupled with the problem of regioselectivity, along with directing group introduction and removal, create a major hurdle, which remains a crucial issue in this approach. [17,18,20] Due to the aforementioned reasons, further discussion of this mode will not be pursued. The second methodology Dr. Jiatong Li earned her M.D.…”
Section: Synthetic Strategies Of Pyridinementioning
confidence: 99%
“…Notwithstanding the diverse range of alternatives offered by CÀ H bond functionalization, coupled with the problem of regioselectivity, along with directing group introduction and removal, create a major hurdle, which remains a crucial issue in this approach. [17,18,20] Due to the aforementioned reasons, further discussion of this mode will not be pursued. The second methodology Dr. Jiatong Li earned her M.D.…”
Section: Synthetic Strategies Of Pyridinementioning
confidence: 99%
“…Pyridine with a six-membered N-heterocyclic structure was usually considered as a good ligand due to strong coordination nature stemming from the pyridine nitrogen. 24 Combining the amide bond linkage moiety of the 2-position in the pyridine skeleton, the compound containing pyridine unit could act as a precursor of difluoroboron compounds. 25 As previously reported, we found that pyridine-based difluoroboron compound with the TPA group at the end of amide bond linkage moiety could be applied in the field of inkless writing.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Thus, the development of effective methods to access pyridine-containing molecules has been a prominent area of research. 3 While one of the most popular approaches involves elaborating the pyridine ring, 4 another valuable strategy includes leveraging this moiety to electronically activate starting materials for stereoselective chemical transformations. 5 Specifically, the CvN moiety within pyridine rings imparts electron-withdrawing properties, augmenting the electrophilicity of adjacent functional groups such as olefins or carbonyls, albeit with a relatively weaker activation compared to isostructural carbonyls.…”
Section: Introductionmentioning
confidence: 99%